Synthesis and in Silico Studies of a Benzenesulfonyl Curcumin Analogue as a New Anti Dengue Virus Type 2 (DEN2) NS2B/NS3 - Ikhtiarudin, Ihsan (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
Curcumin has been reported can interact with multiple molecular targets involved in a large variety of diseases. Accumulated evidence indicated curcumin plays an inhibitory role against infection of numerous viruses. Some studies have been reported that curcumin can interfere the infection processes of dengue virus. In this work, a benzenesulfonyl curcumin, (3E,5E)-3,5-bis(4-methoxybenzylidene)-1-(phenylsulfonyl)piperidin-4-one (compound 2) has been synthesized by two steps of reactions. The structure of compound 2 has been established based on the interpretation of spectral data include UV, FT-IR, MS/MS, 1H and 13C NMR. Then, the in silico studies have been also performed to predict the potency of compound 2 as inhibitor for dengue virus Type 2 (DEN 2) NS2B/NS3 protease. The in silico studies showed that compound 2 has hydrogen bonding with His51 residue, and amazingly that the other catalytic triad such as Asp75 and Ser135 were also showed interactions with the ligand. It is presumably that this compound showed very good activity against DEN2 and can be developed as a new inhibitor for dengue viruses.